Smelting and recycling evidences from the Late Bronze Age habitat site of Baiões (Viseu, Portugal) - Figueiredo, Elin (2013)
Many aspects of bronze production during Late Bronze Age in Western Europe are so far unknown. In the present study selected artefact fragments and metallurgical debris, which include a slag fragment, from the emblematic Late Bronze Age habitat site of Castro da Senhora da Guia de Baio˜es (Viseu, Portugal) have been studied by optical microscopy, micro-EDXRF, SEM–EDS and XRD. Evidences were found for bronze production involving smelting and recycling. Compositional analysis showed that the artefacts are made of a bronze with 133 wt.% Sn (average and one standard deviation) and a low impurity pattern, namely <0.1 wt.% Pb, being comparable with the composition of other bronzes from the same region (the Central Portuguese Beiras). This alloy is generally different from elsewhere Atlantic and Mediterranean bronzes, which show frequently slightly lower Sn contents and higher impurity patterns,namely Pb which is often present as an alloying element. The present study gives further support to early proposals suggesting the exploration of the Western Iberian tin resources during Late Bronze Age, and besides that, it indicates that metalworking and smelting could have been a commonplace activity requiring no speciﬁc facilities, being bronze produced at a domestic scale in this Western extreme of Europe.